Internal migration and labor market adjustments in the presence of non-wage compensation - Raphael Bottura Corbi; Tiago Ferraz; Renata Narita (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2025)
In this paper, we argue that adjustments in non-wage compensation are empirically relevant and have important implications for understanding the effects of labor supply shocks. We examine the labor market impacts of internal migration in Brazil through a shift-share approach, which combines weather-induced migration with historical settlement patterns at each destination. Our findings indicate that increasing migration inflows lead to a reduction in formal employment while simultaneously increasing informality by a similar magnitude. Unlike previous studies, we observe a significant negative impact on earnings within the formal sector. Additionally, we provide evidence that the proportion of formal workers receiving non-wage benefits declines, underscoring that substantial adjustments take place in the formal sector, even in a context of high informality. We interpret our results within a framework where formal and informal labor inputs are imperfect substitutes and where non-wage benefits generate predictions that align closely with our empirical findings.
Keywords: J2; J3; J61; O15; 330; Internal migration; wages; employment; non-wage benefits